Hepatitis-B-associated glomerulonephritis in children - Öner, Ayşe; Tınaztepe, Keriman; Demircin, Gülay (The Turkish Journal of Pediatrics, 1997)
Three cases with hepatitis B virus (HBV)-related, biopsy-diagnosed glomerulopathies, one of which was membranous glomerulonephritis and the others membranoproliferative glomerulonephritis, are reported, emphasizing the clinical course. Two patients had spontaneous remission after seroconversion to anti-HBe-positivity, while the third patient was lost to follow-up. We reviewed the management of HBV-associated glomerulonephritis and concluded that immunosuppressive drugs should be avoided since spontaneous remission can be expected in these types of glomerulopathies.